Hegemonic Age Restriction Law in Labor Recruitment - Sabrina Deviana; Herdiansyah Hamzah; A. Alfian (Manunggal Halim Jaya, 2026)
Every individual has the right to decent work and fair employment conditions. However, many Indonesian citizens face difficulties in obtaining employment due to age restrictions imposed during recruitment, despite having adequate skills and productivity. This study aims to analyze the legal politics of age limitations in labor recruitment and examine their implications for employment policies. Using a socio-legal research method, this study combines normative legal analysis with social and non-legal approaches, supported by statutory and legal theory perspectives. The findings indicate that assumptions of lower productivity and higher operational costs often justify age restrictions. Such practices limit employment opportunities and potentially violate constitutional principles of equality and non-discrimination.